2006
DOI: 10.1002/hep.21261
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between beta-lipoprotein levels and outcome of hepatitis C treatment

Abstract: H epatitis C viral infection is a common cause of chronic liver disease, with a worldwide prevalence of 3%. About 140 million people worldwide and 4 million in the United States are infected with HCV. An estimated 65% to 80% of the individuals infected with HCV develop persistent infection. As many as 20% to 50% of these individuals develop cirrhosis and 5% develop hepatocellular carcinoma. 1,2 The rate of disease progression varies widely, and unknown factors other than alcohol use, obesity, and age may influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
94
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 26 publications
16
94
1
Order By: Relevance
“…These data suggested a possible interaction between TC and HCV infection. Our speculations were supported by recent data that higher TC and LDL levels are associated with a better therapeutic outcome of chronic hepatitis C [40].…”
Section: Discussionsupporting
confidence: 85%
“…These data suggested a possible interaction between TC and HCV infection. Our speculations were supported by recent data that higher TC and LDL levels are associated with a better therapeutic outcome of chronic hepatitis C [40].…”
Section: Discussionsupporting
confidence: 85%
“…Smaller previous studies have suggested that this might be the case for LDL, 3,4 but this is the largest trial to date to corroborate these findings and the first published study to our knowledge to show a relationship between HDL and SVR. In a small retrospective study, Gopal et al 4 found that, among patients with EVR, EOT response, and SVR, the LDL and total cholesterol levels were higher, and this was independent of age. 4 Subsequently, Akuta et al 3 found that an LDL level !…”
Section: Discussionsupporting
confidence: 65%
“…In a small retrospective study, Gopal et al 4 found that, among patients with EVR, EOT response, and SVR, the LDL and total cholesterol levels were higher, and this was independent of age. 4 Subsequently, Akuta et al 3 found that an LDL level ! 86 mg/dL was an independent predictor in a multivariate logistic regression analysis of EVR and SVR in 114 Japanese adults with HCV genotype 1 who were treated with PEG-IFN and RBV for 48 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low levels of LDL are caused by geranylgeranyl-diphosphate in viral replication, which is a substrate for the synthesis of cholesterol. The high levels of LDL compete with LDL receptors and reduce viral replication, whilst the high levels of HDL aid the entry of the virus into the hepatocyte (24). In the hepatocyte, HCV interferes with the lipid metabolism of the host to replicate and assemble leading to hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%